Water Permeability of Cochlear Outer Hair Cells: Characterization and Relationship to Electromotility - Belyantseva, Inna A. (J Neurosci, 2000)
The distinguishing feature of the mammalian outer hair cells (OHCs) is to elongate and shorten at acoustic frequencies, when their intracellular potential is changed. This “electromotility” or “electromechanics” depends critically on positive intracellular pressure (turgor), maintained by the inflow of water through yet uncharacterized water pathways. We measured the water volume flow,J(v), across the plasma membrane of isolated guinea pig and rat OHCs after osmotic challenges and estimated the osmotic water permeability coefficient,P(f), to be ∼10(−)(2) cm/sec. This value is within the range reported for osmotic flow mediated by the water channel proteins, aquaporins. J(v) was inhibited by HgCl(2), which is known to block aquaporin-mediated water transport. P(f)values that were estimated for OHCs from neonatal rats were of the order of ∼2×10(−)(3) cm/sec, equivalent to that of membranes lacking water channel proteins. In an immunofluorescence assay we showed that an anti-peptide antibody specific for aquaporins labels the lateral plasma membrane of the OHC in the region in which electromotility is generated. Using patch-clamp recording, we found that water influx into the OHC is regulated by intracellular voltage. We also found that the most pronounced increases of the electromotility-associated charge movement and of the expression of OHC water channels occur between postnatal days 8 and 12, preceding the onset of hearing function in the rat. Our data indicate that electromotility and water transport in OHCs may influence each other structurally and functionally.